Depressão atual, uso de antidepressivo e marcador inflamatório: estudo longitudinal de saúde do adulto (Elsa-Brasil) - Sara Teles de Meneses (2015)
BACKGROUND: Studies on rural populations have shown the association of depression with the rise of various inflammatory markers, but the results are inconsistent. The use of antidepressants also shows association with inflammatory markers, but seems to vary according to the drug class. OBJECTIVES: This thesis has three objectives, namely: 1) To investigate whether there is an association of depression with current CRP levels independently of the presence of other covariates of confusion in the cohort participants. 2) To investigate whether thereis an association of antidepressant use with CRP levels independently of the presence of depression and other covariates of confusion in the cohort participants. 3) To investigate whether there is an association of different classes of antidepressants with CRP levels, after adjustment for covariates of confusion. METHODS: The sample is from the baseline of the Adult Health Longitudinal Study ELSA-Brazil, consisting of 15 105 adult participants and the elderly, public servants higher education and research institutions in six Brazilian states: Minas Gerais, São Paulo,Rio de Janeiro, Espírito Santo, Bahia and Rio Grande do Sul. The article developed it is a sectional analysis of 14,821 participants (35-74 years) from baseline (2008-2010) of the cohort ELSA-Brazil. The depression in the last 7 days (yes / no), assessed by the Clinical Interview Schedule-Revised, combined or not with the use of antidepressants (yes / no) was the main explanatory variable and serum CRP levels, the response variable. Sociodemographic characteristics, health behaviors and comorbidities were the covariates. It also assessed whether any antidepressant class was independently associated with CRP levels. The reasons for arithmetic means (RMA) and 95% confidence intervals were estimated using the general linear model (GLM) using theGamma distribution and log link function. RESULTS: After adjustment for sex, age and education, or depression alone or associated with antidepressant use or the use of isolated antidepressant remainedstatistically associated with high CRP levels. The entry of other adjustment factors in the multivariate model (health-related behaviors and the presence of morbidities) did not alter this result. The same result occurred in the analysis according to the type and severity of depression and stratification by sex. Restricting analysis to those with CRP less than 10 mg / dL, or did not use anti-inflammatory and excluding women using contraceptives and hormone replacement therapy did not alter the results above. CONCLUSION: The results of this study showed that, after adjustment for important confounding factors, or the current depression, or the use of antidepressants in combination or separately, were statistically associated with higher CRP levels and that this result has remained unchanged in stratified analysis by gender. The results of thisstudy are consistent with some studies published in the literature and disagree with previous studies also carried out in general populations linking depression to high levels of different inflammatory markers. Our results thus suggest that it is possible that the lifestyle, underlying medical conditions, use of other medications, presence indicationbias and different methodological strategies can explain the inconsistencies in the investigations on the use of antidepressants and inflammatory markers, particularly PCR, in studies conducted in the general population. The presence of individuals with depression in the past year or life among depressed can not have contributed to dilute anassociation, if any.